Professionalism and Professional Ethics: Representative Perspectives of Social Researchers in Vietnam - Hoang, Minh Ngoc (Journal of Contemporary Issues in Education, 2025)
Professionalism has always been an influential concept in the social sciences. However, its definition and characteristics constantly require cross-checking and modification to adapt to the growing multifaceted contexts in modern times. This paper offers a small-scale qualitative study examining the perceptions of professionalism and professional ethics of the social research community in Vietnam to understand and acknowledge their contextual conditions and hardships. The findings reveal the complex situation of social researchers in Vietnam, which demands that they respond to external pressures and requirements while maintaining professional ethics and good consciousness. Locally, two corresponding issues are highlighted: unsatisfactory education and training and a lack of motivation for long-term changes. More broadly, the paper proposes a theory of selective motivations and a set of extensive tools, adapted from existing literature, to effectively address professionalism from a marginalized perspective.